China: Crônica de um país em rápida transformação - Marcelo Pires Negrão (Confins)
This recite presents the impressions experienced during a teaching stay and a visit to the two major Chinese metropolises, Shanghai and Beijing, between May and June, 2019. It describes the rapid transformations of the country, the emerging condition of these globalized cities, and Chinese behavior seen through the eyes of an occidental.